2018
DOI: 10.1177/0886260518807216
|View full text |Cite
|
Sign up to set email alerts
|

Educational Attainment of Male Homicide Victims Aged 18 to 24 Years in Chicago: 2006 to 2015

Abstract: Homicide is a preventable public health issue that has detrimental effects on both victims and witnesses and increases health care costs. From 2006 to 2015, homicide has been the second leading cause of death for youth aged 15 to 24 years in the United States. Educational attainment has been widely regarded as a protective factor against justice system involvement and violent injury. We conducted a time-trend analysis examining educational attainment levels for male victims of homicide aged 18 to 24 years in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Previously, Pardini and colleagues examined effects of educational achievement on violence in youth aged 13-18 enrolled in Pittsburgh public schools and found no significant effect after controlling for demographic and socioeconomic variables (Pardini et al, 2012). Similarly, Hazekamp and colleagues examined the impact of high school educational achievement in Chicago on youth homicide rates and found that youth homicide continued to increase locally despite increases in educational achievement (Hazekamp et al, 2018). The authors suggested the contagious nature of violence, spreading through social networks, undermines education's protective effect during this time, highlighting the importance of reducing violence exposure during this vulnerable period (Hazekamp et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, Pardini and colleagues examined effects of educational achievement on violence in youth aged 13-18 enrolled in Pittsburgh public schools and found no significant effect after controlling for demographic and socioeconomic variables (Pardini et al, 2012). Similarly, Hazekamp and colleagues examined the impact of high school educational achievement in Chicago on youth homicide rates and found that youth homicide continued to increase locally despite increases in educational achievement (Hazekamp et al, 2018). The authors suggested the contagious nature of violence, spreading through social networks, undermines education's protective effect during this time, highlighting the importance of reducing violence exposure during this vulnerable period (Hazekamp et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hazekamp and colleagues examined the impact of high school educational achievement in Chicago on youth homicide rates and found that youth homicide continued to increase locally despite increases in educational achievement (Hazekamp et al, 2018). The authors suggested the contagious nature of violence, spreading through social networks, undermines education's protective effect during this time, highlighting the importance of reducing violence exposure during this vulnerable period (Hazekamp et al, 2018). Perhaps consistent with these findings, the present investigation did not find significant direct effects of eighth grade educational achievement in adjusted models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of acknowledgment of these structural factors further masks other determinants of premature death impacting the low life expectancy of young Black males. Their troubling educational underachievement, poverty, unemployment, HIV/AIDS, cardiovascular disease, prediabetes, obesity, and smoking (e.g., cigarettes and marijuana) have been found to be factorial threats to their health and lead to premature deaths (Hazekamp et al, 2018; Jones-Eversley & Ravenell, 2018; Montgomery et al, 2019; Pathak, 2018).…”
Section: Peer-to-peer Homicidementioning
confidence: 99%